Hubungan Kualitas Layanan dengan Minat Kunjung Pemustaka di Perpustakaan Kota Bandung - Muhammad Fadhiil Insan Kamil; Prijana; Kurniasih, Nuning (Literatify: Trends in Library Developments, 2024)
The library is one of the sources of information and science that has an important role in supporting education, research, and the development of society. One of the indicators of success in the library is the high level of interest in visiting librarians. This research aims to find out how much the quality of the service is linked to the interest of visiting librarians in the Bandung City library. The sampling technique in this study used quota samplings, with a quantitative approach to 43,338 library visitors in January – November 2023 and a sample of 300 respondents. An analysis conducted using the Software Statistical Package for The Social or SPSS version 27 resulted from the results of this study that the quality of the service has an influence with the interest of the publisher with the acquisition of numbers of 0.629 or in the level of “strong ” relationship. The highest variable is obtained by the physical evidence (tangible) of 0.506 then followed by reliability of 0.450, assurance of 0,425, responsiveness of 0.406, and finally empathy of 0.376